A novel GCGR/GLP-1R dual-agonist TB001 ameliorates kidney fibrosis via inhibiting PERK-mediated endoplasmic reticulum stress pathway - Lai, Weijie; Peng, Linjie; Min, Jianliang; Qiu, Longhui; Wang, Chang; Yu, Shuangjin; Li, Qihao; Li, Ruobing; Jiang, Xianxing; Chen, Guodong (Frontiers in Immunology, 2025)
BackgroundChronic kidney disease (CKD) affects over one million individuals worldwide and remain a critical economic and healthcare burden. Renal fibrosis is the hallmark of CKD. Previous reports showed that GLP-1R agonists could help prevent kidney fibrosis in diabetic patients. In this study, we aimed to determine the efficacy of a novel GLP-1R and GCGR co-agonist, TB001 in the development of renal fibrosis using both in vitro and in vivo models.MethodsUnilateral ureteral obstruction (UUO) surgery was performed on adult B6 mice to establish a mouse model of kidney fibrosis. Mice that underwent sham surgery served as the control group. UUO mice were treated with vehicle or TB001 daily post-surgery and were sacrificed at day 14. Tissue samples were collected for immunohistochemistry and kidney mRNA gene expression analysis. Mouse tubular cells (mTECs) stimulated with TGF-β were used to model kidney fibrosis in vitro.ResultsCompared with vehicle treatment, TB001 treatment significantly improved renal histopathology and reduced interstitial collagen deposition and macrophage infiltration in obstructed kidneys. Both in vitro and in vivo data suggested that TB001 treatment significantly inhibited tubular cell epithelial-mesenchymal transition (EMT). Moreover, the obstructed kidneys in the TB001 treatment group showed significantly fewer PERK and p-eIF2α positive cells than compared to those in the vehicle group, indicating that PERK-mediated ER stress may be involved in the protective effect of TB001 on renal fibrosis. These data were corresponding with the vitro results showing that TB001 significantly suppressed the expression of PERK and CHOP and enhanced mitochondrial mass during TGF-β induced EMT.ConclusionThis study demonstrated that TB001, a novel GCGR/GLP-1R co-agonist, effectively attenuates renal fibrosis in pre-clinical models, potentially through the inhibition of PERK-mediated ER stress in tubular cells.